Disorders of Calcium and Phosphorus Metabolism and the Proteomics/Metabolomics-Based Research - Sun, Meiheng; Wu, Xiaoqiu; Yu, Yuanyuan; Wang, Luyao; Xie, Duoli; Zhang, Zhenlin; Chen, Lin; Lu, Aiping; Zhang, Ge; Li, Fangfei (Frontiers in Cell and Developmental Biology, 2020)
Since calcium and phosphorus play vital roles in a multitude of physiologic systems, disorders of calcium and phosphorus metabolism always lead to severe consequences such as skeletal-related and cardiovascular morbidity，or even life-threatening. Physiologically, the maintenance of calcium and phosphorus homeostasis is achieved via a variety of concerted actions of hormones such as parathyroid hormone (PTH), vitamin D, and fibroblast growth factor (FGF23), which could be regulated mainly at three organs, the intestine, kidney, and bone. Disruption of any organ or factor might lead to disorders of calcium and phosphorus metabolism. Currently, lacking of accurate diagnostic approaches and unknown molecular basis of pathophysiology will result in patients being unable to receive a precise diagnosis and personalized treatment timely. Therefore, it is urgent to identify early diagnostic biomarkers and develop therapeutic strategies. Fortunately, proteomics and metabolomics offer promising tools to discover novel indicators and further understanding of pathological mechanisms. Therefore, in this review, we will give a systematic introduction on PTH-1,25(OH)2D-FGF23 axis in the disorders of calcium and phosphorus metabolism, and diagnostic biomarkers identified and potential altered metabolic pathways involved.